Journey of DNA Evidence in Legal Arena: An Insight on Its Legal Perspective Worldwide and Highlight on Admissibility in India - Ramakant Gupta; Swati Gupta; Manju Gupta (Wolters Kluwer Medknow Publications, 2016)
DNA profiling is one of the powerful breakthroughs in forensics. This specialized technique has made the identification of an individual possible even by a tiny shred of tissue or drop of blood thus, has strongly revolutionized various criminal investigations. Rape, paternity, and murder cases are the type of criminal cases commonly solved by the use of this technique. It has been recently introduced to forensic odontology and is also used frequently. Although this is a powerful and reliable scientific technique but its forensic use is a major contribution to the debate on law reform. The application of DNA profiling in the criminal justice system, i.e., the admissibility of DNA evidence in court of law is an important issue which is being faced by the courts and forensic experts worldwide today. Thus, a proper legal outlook is required while dealing with this kind of scientific evidence. Therefore, this review intends to make forensic experts/odontologists aware about the admissibility of DNA evidence in court, with a highlight on the laws related to the admissibility of evidence worldwide, having a special focus on the laws related to admissibility of evidence in Indian judicial system. For this review, the literature was overviewed from articles on DNA evidence and admissibility retrieved by searches on electronic databases such as Google, PubMed, and EMBASE from 1975 through July 2015.